Epilepsy prevalence and socioeconomic deprivation in England. Issue 10 (2nd September 2014) - Steer, Samuel; Pickrell, William O.; Kerr, Michael P.; Thomas, Rhys H.
Summary Objective Epilepsy is more prevalent in areas of greater socioeconomic deprivation; however, the factors that comprise this deprivation are not understood. We aimed to investigate the association between epilepsy, individual elements of deprivation, and geographic region in order to identify modifiable elements. Methods Epilepsy prevalence was calculated via retrospective analysis of data recorded by general practitioners via the Quality and Outcomes Framework. The Index of Multiple Deprivation scores at Local Authority level for the entire population of England was employed. Epilepsy prevalence was evaluated for correlation against all seven indicators within the Indices of Multiple Deprivation. Data were analyzed including and excluding the city of London. Results Of the 37, 699, 503 patients in this study, 304, 331 were registered as having epilepsy (prevalence 8 per 1, 000; range 4.3–11.6). Positive correlation was seen with total Index of Multiple Deprivation score (r = 0.468, p < 0.01); education skills and training (r = 0.665, p < 0.01); employment deprivation (r = 0.629, p < 0.01); health deprivation and disability (r = 0.617, p < 0.01); income deprivation (r = 0.358, p < 0.01); crime (r = 0.232, p < 0.01); but not living environment (r = 0.079, p = 0.08). Negative correlation was seen between epilepsy prevalence and barriers to housing and services (r = −0.415, p < 0.01). When the data were analyzed excluding London, all correlations were strengthened. Epilepsy prevalence in adults varies by 2.5‐fold across England, from 4.3 per 1, 000 in Kensington and Chelsea to 11.6 per 1, 000 in Blackpool. Significance This study shows a strong correlation between epilepsy prevalence and specific measures of socioeconomic deprivation. Many of these deprivation factors are potentially remediable. We hypothesize that people with epilepsy may move into urban areas and toward their general practitioner. This predominantly means an urban location but avoiding areas where the cost of living—particularly housing—is prohibitive, such as central London. The existing negative impact of epilepsy on employment and higher education may be exacerbated when people with epilepsy live in areas of greater socioeconomic deprivation.